Dying for survival: Why militant organizations continue to conduct suicide attacks. (March 2016) - Acosta, Benjamin
Suicide attacks continue to plague a multitude of conflict zones. However, the scholarly literature on the phenomenon has yet to produce a theory that explains why militant organizations at different stages of development, facing dissimilar enemies, and situated in unique conflict environments adopt suicide attacks. Moreover, the suicide-attack phenomenon now presents an intriguing puzzle. While most militant organizations fail to achieve their core political ends or 'outcome goals', organizations that employ suicide attacks are even less likely to succeed. Still, organizations have adopted suicide attacks at increasing rates. Given their ineffectiveness in precipitating outcome-goal success, why do organizations continue to adopt suicide attacks? Like all organizations, militant organizations share two common aims: (1) to survive and (2) to achieve outcome goals. As martyrdom operations often fulfill the ideological or cultural expectations of certain identity groups, representative organizations may adopt suicide attacks to expand constituent support or enhance status within a particular political landscape. Further, organizations can conduct suicide attacks to signal ideological solidarity with fellow militant organizations. This article analyzes an original large-N dataset of militant organizations alongside an original database of over 5, 000 suicide attacks, and evaluates numerous case examples. The results demonstrate that militant organizations across regions and over time have adopted suicide attacks in order to gain supporters, promote organizational longevity, and boost or preserve status.